Engaged surrender : African American women and Islam - Rouse, Carolyn Moxley, 1965- (George Gund Foundation imprint in African American studies., 2004)
Commonly portrayed in the media as holding women in strict subordination and deference to men, Islam is nonetheless attracting numerous converts among African American women. Are these women ""reproducing their oppression, "" as it might seem? Or does their adherence to the religion suggest unsuspected subtleties and complexities in the relation of women, especially black women, to Islam? Carolyn Rouse sought answers to these questions among the women of Sunni Muslim mosques in Los Angeles. Her richly textured study provides rare insight into the meaning of Islam for African American women; in.